THE EFFECT OF DEFERRED TAX CHARGE, TAX PLANNING AND DEFERRED TAX ASSETS ON PROFIT MANAGEMENT (EMPIRICAL STUDY OF MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2018 – 2021 PERIOD) - Andani, Agnes Tiwan; Damayanty, Prisila (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to examine the effect of deferred tax expense, tax planning and deferred tax assets on earnings management. The population in this study are all property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. Sampling in this study used a purposive sampling method so as to get a sample of 15 companies as a research sample. The data analysis method in this study uses multiple linear regression analysis with SPSS Version 26. The results of this study indicate that deferred tax expense, tax planning have a significant effect on earnings management. Meanwhile, deferred tax assets have no significant effect on earnings management, and deferred tax expenses, tax planning and deferred tax assets have a significant effect on earnings management. Keyword : Deferred Tax Expenses, Tax Planning, Deferred Tax Assets and Profit Management.